PRACTICAL ISSUES OF APPLICATION OF LABOR CODE OF THE REPUBLIC OF KAZAKHSTAN - Nurgaliyeva, Енлик Нургалиевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article analyzes the practice of certain labor disputes resolution which causes different problems because of indefinite expressions and gaps in labor legislation. Particularly special attention is given to conditions of termination of the employment contract under article 52 (item 4) of Labor Code as well as issues of non-disclosure of commercial information.